Analisis Semiotika Kata “Mulatto” Pada Lirik Lagu “Smell Like Teen Spirit” Karya Nirvana - Corniawan, Deddy; Riyanto, Buddy; Muadz, Muadz (Solidaritas, 2024)
This research aims to uncover the true meaning of the word "mulatto" in the lyrics of the song"Smells Like Teen Spirit" by Nirvana. The research method used in this study is qualitativedescriptive research. The semiotic analysis theory used is the semiotic analysis of Ferdinand deSaussure. The concepts used in this research are signifier and signified. The signifier is the word"mulatto" in the lyrics of the song "Smells Like Teen Spirit" by Nirvana. Meanwhile, thesignified functions to represent the concept of the signifier, which in this case is the actualmeaning. The relationship between the signifier and the signified must be connected to each otherin order to produce meaning from the sign. This research seeks the true meaning of the term"mulatto" by examining three interpretations. The interpretation obtained from primary andsecondary data. Meanwhile, the data collection techniques used are documentation study andliterature study. The interpretations obtained include the word "mulatto" as an alcohol, drugs,and race. From the three interpretations that have been studied, it will yield true meaning of theword "mulatto”.2Keywords: Mulatto, Analysis, Signs